Students’s Mathematical Connection Ability and Disposition Reviewed by Keirsey Personality Type through Eliciting Activities Mathematics Learning Model - Prasetyo, Ari; Dwidayati, Nur Karomah; Junaedi, Iwan (Unnes Journal of Mathematics Education, 2017)
The purpose of this research was to described connection mathematical ability and mathematical disposition of seventh grade students of Junior High School reviewed by Keirsey Temperament Sorter (KTS) were Artisans, Idealist, Guardian, and Rational personality in Eliciting Activities Mathematics Learning Model. And was to described the quality of Eliciting Activities Mathematics Learning Model in connection mathematical abilities and the disposition. The subject of research are the two students in each category of personality types. So the subject of this study are 8 student of class VII B SMP Negeri 1 Selogiri 2015/2016. The results Showed a description of (1) the quality of Eliciting Activities Mathematics Learning Model was fine qualified learning model (2) the mathematical connection abilities of (a) Artisan student in succed 1 - 2 indicators means the category is medium, as a level as their mathematical disposition level (b) Guardian students in the category of low, succed only 1 indicator and the rate of disposition was medium (c) Idealist students succed 3-4 indicators and very high levels to the mathematical dispositions (d) Rational students suceed all indicators and entry high level of the mathematical disposition.